PENERAPAN PEMBELAJARAN BERBAGI PENGETAHUAN SECARA AKTIF BERBANTUKAN LKS TERHADAP HASIL BELAJAR IPA FISIKA SISWA KELAS VIII SMPN 3 LENGAYANG - Lora Pragusti Miza (Universitas Negeri Padang, 2014)
Giving directly information from teacher resulted teacher-centered learning so that students become less active because students just sit and listen to the teacher’s explanation. Furthermore, teaching materials used have not been linked to the fact in the life. Effect this situation was student’s learning outcomes to be low. Researcher are interested to see the effect of the application share knowledge actively learning assisted by worksheet on natural science learning outcome of students of class VIII SMPN 3 Lengayang. Type of research is quasi-experimental study with a Randomized Control Group Only Design. Population of this study were student of class VIII SMPN 3 Lengayang. Sampling was used by cluster random sampling technique. The research data includes learning outcome of cognitive and affective. The research instrument is a test of learning outcomes in the cognitive and the affective domain observation sheet. Conclusion of the research is there is a significant effect of the aplication share knowledge actively learning assisted by worksheet on science physics learning outcomes of students of class VIII SMPN 3 Lengayang